Map Ideal of Type the Domain of r-Cesàro Matrix in the Variable Exponent ℓt. and Its Eigenvalue Distributions - Awad A. Bakery; OM Kalthum S. K. Mohamed (Journal of Function Spaces)
In this article, we define a new sequence space generated by the domain of r-Cesàro matrix in Nakano sequence space. Some geometric and topological properties of this sequence space, the multiplication maps defined on it, and the eigenvalue distributions of map ideal with s-numbers that belong to this sequence space have been examined.